Optimizatsiya trenirovochnogo protsessa gimnastok v podgotovitel'nom periode - Abu Alkeshek, M. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of the given study was to elaborate training programs and complexes of recovery aids for training process'es optimization in female gymnasts 15-16 years of age on preparation period of a year cycle. The modern training programs forvarious microcycles of the preparation period of femal gymnasts training had been elaborated and tested. Two special recovery complexes had been created which included the pedagogical, gygienic, medico-biological and psychological means of the sports working capacity's increase.